Analisis Integrasi Nilai-Nilai Penguatan Pendidikan Karakter Pada Buku Tematik Siswa Kelas 3 Tema 4 Kewajiban dan Hakku - Rahmad Widhianto; Mohammad Aniq Khairul Basyar; Asep Ardiyanto (STKIP Andi Matappa Pangkep, 2021)
Character strengthening education in curriculum 2013 integrated to all of formal education aspects in Indonesia, the one of it is student thematic book that used as learning media in the school. The purpose that to be achieved in this research is the writer want to know the value integration of character strengthening education in the student thematic book grade 3 theme 4